More Than Just Black and White: A Case for Grey Literature References in Scientific Paper Information Retrieval Systems - Sesagiri Raamkumar, Aravind (2015)
In this paper, we start by analyzing the presence of grey literature (GL) references in the bibliographies of different article-types using an extract of 122,406 articles from the ACM Digital Library. GL articles accounted for about 16% of the overall references with highest presence in proceedings (17.61%). Boosting techniques for promoting GL references are proposed for information retrieval systems for two specific scenarios. A simple IR experiment was conducted with 103,739 articles to validate the proposed boosting techniques with 10 research topics. Results show that GL references were consistently pushed to the top of the search results along with an increased visibility in top 20 results.